2017
DOI: 10.4081/ejh.2017.2732
|View full text |Cite
|
Sign up to set email alerts
|

The possible prognostic role of histone deacetylase and transforming growth factor β/Smad signaling in high grade gliomas treated by radio-chemotherapy: a preliminary immunohistochemical study

Abstract: Glioblastoma (GBM) is the most common and aggressive tumor of the central nervous system. Unfortunately, patients affected by this disease have a very poor prognosis, due to high level of invasiveness and resistance to standard therapies. Although the molecular profile of GBM has been extensively investigated, the events responsible for its pathogenesis and progression remain largely unknown. Histone Deacetylases (HDAC) dependent epigenetic modifications and transforming growth factor (TGF)-β/Smad pathway seem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 37 publications
0
21
0
Order By: Relevance
“…16,23 Highly expressed HDAC4 is positively correlated with the tumor grade and negatively correlated with overall survival rates. 40,41 Recently, HDAC4-mediated transcriptional suppression of p21 expression has been found to contribute to malignant proliferation of gliomas, 23 as well as other cancer cells, including breast cancer, 42 colon cancer 43 and lung adenocarcinoma, 44 implying that HDAC4 nuclear import is most likely predominant due to its role in tumorigenesis. Through IHC analysis, we found that the rates of nuclear HDAC4 significantly increased among Grade II, III and Grade IV glioma samples and were positively correlated with the grades.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16,23 Highly expressed HDAC4 is positively correlated with the tumor grade and negatively correlated with overall survival rates. 40,41 Recently, HDAC4-mediated transcriptional suppression of p21 expression has been found to contribute to malignant proliferation of gliomas, 23 as well as other cancer cells, including breast cancer, 42 colon cancer 43 and lung adenocarcinoma, 44 implying that HDAC4 nuclear import is most likely predominant due to its role in tumorigenesis. Through IHC analysis, we found that the rates of nuclear HDAC4 significantly increased among Grade II, III and Grade IV glioma samples and were positively correlated with the grades.…”
Section: Discussionmentioning
confidence: 99%
“…In glioma cells, HDAC4 activity has been implicated in invasion, proliferation, and drug and radiation resistance . Highly expressed HDAC4 is positively correlated with the tumor grade and negatively correlated with overall survival rates . Recently, HDAC4‐mediated transcriptional suppression of p21 expression has been found to contribute to malignant proliferation of gliomas, as well as other cancer cells, including breast cancer, colon cancer and lung adenocarcinoma, implying that HDAC4 nuclear import is most likely predominant due to its role in tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…In breast cancer, the involvement of HDAC6 in the Hippo pathway-regulating network was demonstrated by downregulation of YAP protein levels [53] and by a strong acetylation and destabilization of the tumor suppressor MST1 [54]. Some evidence suggests that HDAC6 plays a role in theTGFβ−SMAD activation pathway, and thus its inhibition establishes a decrease in EMT induction [55,56]. Finally, most recently, it has been shown that HDAC6 inhibition leads to inactivation of Gli1, resulting in glioma cancer cell radio-sensitization [57].…”
Section: Histone Deacetylase (Hdac) Inhibitors Target Cancer Stem mentioning
confidence: 99%
“…Previous studies in non-CNS tumors, aimed to identify targets for radiosensitization using siRNA and shRNA-mediated knockdown of individual HDAC isoforms, revealed HDACs class IIa as potential targets for pharmacologic inhibition 12,34–38 . Recently, it was demonstrated that that the level of HDAC4 expression of GBMs negatively correlates with overall survival rates after temozolomide and radiation therapy 39,40 . Moreover, high HDAC4 expression was found to be a strong predictive factor of poor outcome of TMZ treatment of GBM, independent of MGMT status and Ki67 index.…”
Section: Introductionmentioning
confidence: 99%